Overview of Nanopesticide Environmental Safety Aspects and Regulatory Issues: The Case of Nanoatrazine - de Albuquerque, Felícia Pereira [UNESP]; Preisler, Ana Cristina; Fraceto, Leonardo F. [UNESP]; Oliveira, Halley Caixeta; de Castro, Vera Lucia S. S. (Springer Nature, 2020)
The use of nanotechnology to create new formulations has shown great potential to reduce the indiscriminate use of pesticides and provide environmentally safer alternatives. Pesticides formulated using controlled release nanosystems are designed to efficiently provide sufficient and targeted quantities of active ingredients to target organisms, thus improving crop yields and reducing environmental contamination with pesticides. However, the possible harmful effects of these nanomaterials on the environment are not yet well understood, highlighting the need for studies assessing the fate and behavior of nanopesticides in the environment. This chapter will discuss the major challenges and advances in the research regarding nanopesticide risk analysis. It will also discuss the difficulty in developing regulations about the commercialization of nanoproducts, due to the underlying specific features of nanomaterials that drive their reactivity and toxicity. Finally, the case of nanoatrazine will be reviewed, providing an example of how the nanoencapsulation can affect herbicide efficiency and influence its toxicity to different non-target organisms.
Keywords: Atrazine; Ecotoxicology; Nanoherbicide; Nanotechnology; Risk